2020
DOI: 10.1002/advs.201902071
|View full text |Cite
|
Sign up to set email alerts
|

Anomalously Suppressed Thermal Conduction by Electron‐Phonon Coupling in Charge‐Density‐Wave Tantalum Disulfide

Abstract: Charge and thermal transport in a crystal is carried by free electrons and phonons (quantized lattice vibration), the two most fundamental quasiparticles. Above the Debye temperature of the crystal, phonon‐mediated thermal conductivity (κL) is typically limited by mutual scattering of phonons, which results in κL decreasing with inverse temperature, whereas free electrons play a negligible role in κL. Here, an unusual case in charge‐density‐wave tantalum disulfide (1T‐TaS2) is reported, in which κL is limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…2d). Similar properties were also found in metallic transition-metal nitrides [56] and the charge-density-wave material 1T-TaS2 [57].…”
Section: ⅲ1 Imaginary Part Of Phonon Self-energy: Phonon Scattering B...supporting
confidence: 74%
“…2d). Similar properties were also found in metallic transition-metal nitrides [56] and the charge-density-wave material 1T-TaS2 [57].…”
Section: ⅲ1 Imaginary Part Of Phonon Self-energy: Phonon Scattering B...supporting
confidence: 74%
“…Liu et al measured the thermal conduction of 1T-TaS 2 only recently and reported an anomalous suppression caused by strong electron-phonon coupling. 34 Additionally, they reported intriguing near temperature (T )-independent κ ph , which could possibly be related to the indirect evaluation of κ ph , namely by subtract-ing κ e , estimated Wiedemann-Franz law (WFL), from κ total . The WFL gives κ e = LσT, where σ is the electrical conductivity and the Lorenz ratio L is assumed to be the Sommerfeld value L 0 .…”
mentioning
confidence: 99%
“…64 The real part leads to a renormalization of the phonon frequency while the imaginary part modifies the phonon lifetime by introducing an extra source of phonon scattering and can lead to a reduction of the thermal conductance. Recently, this reduction in phonon transport due to EPI has been both experimentally measured 65,66 and computationally predicted. 67–70…”
Section: Recent Advances In Understanding Interfacial Thermal Transportmentioning
confidence: 97%